Factors Influencing Real Estate Value And Their Consideration In The Valuation Process - Fayziyeva Gulnoza Abdurahmonovna (Periodica Journal, 2025)
This article analyzes the main factors influencing real estate value, their economic and social importance, and the mechanisms for accounting for these factors in the valuation process. The study identifies that factors such as location, infrastructure development, environmental conditions, natural and seismic safety, ecological cleanliness, and transportation accessibility directly and indirectly affect real estate market value. Methods for determining the degree of influence through coefficients and integrating them into the final valuation are described. The research results show that ecological conditions, infrastructure potential, and seismic stability are among the key determinants of real estate value. Moreover, considering health, living comfort, and safety indicators allows for a more realistic and objective valuation of the property
Keywords: Real estate; valuation process; factors; economic analysis